High-performance high-temperature-resistant dual-modified Al2O3-SiO2 composite aerogel and preparation method thereof
By adding organosilane modifiers in the sol stage and performing deposition modifications in the aging stage, the gel network structure is optimized, and the problems of Al2O3-SiO2 aerogel sintering and pore structure collapse at high temperatures are solved, and a high-performance, high-temperature-resistant aerogel materials are realized.
Patent Information
- Application Number
- CN202510095227.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
AI Technical Summary
The existing Al2O3-SiO2 aerogel exhibits problems such as sintering, shrinkage and pore structure collapse at high temperatures, resulting in a decrease in its heat resistance and thermal insulation performance, limiting its application at higher temperatures.
By adding an organic silane modifier in the sol stage and performing deposition modification in the aging stage, the gel network structure is optimized to improve the high temperature stability and thermal insulation performance of the material.
High performance high-temperature resistant dual-modified Al2O3-SiO2 composite aerogel with high specific surface area, high pore capacity and low thermal conductivity is achieved, and can maintain good physical performance above 1200°C.
Smart Images

Figure CN119873865A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal insulation materials, and specifically relates to a high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel and a preparation method thereof. Background Art
[0002] The continuous and irregular three-dimensional nano-network structure of SiO2 aerogel is the key to its super thermal insulation performance. However, at high temperatures, the necks where the primary particles contact each other shrink, causing shrinkage and clustering. This leads to sintering of the particles, destruction of the nanopore structure, and a tendency for the material to become dense. The heat-resistant temperature is only 800°C, and the long-term use temperature in an aerobic environment does not exceed 650°C, which greatly limits the application of SiO2 aerogel in high-temperature fields. Alumina aerogel still does not undergo significant sintering and shrinkage at 1000°C and maintains a nanopore network structure and a high specific surface area (~400m 2 / g), is an aerogel material with outstanding temperature resistance in an aerobic environment, and has broad application prospects in high-temperature insulation, catalysis, adsorption and other fields. However, alumina aerogel will undergo significant sintering and phase change above 1000°C, accompanied by volume shrinkage and collapse of pore structure, as well as a decrease in specific surface area and performance, which greatly limits the application of alumina aerogel at higher temperatures (1200°C and above). In recent years, SiO2 has been introduced to the surface of alumina particles. Since SiO2 forms a thin SiO2 layer on the surface of alumina gel particles, the introduction of SiO2 can inhibit the phase change and crystallization of alumina aerogel, but the specific surface area and pore volume of Al2O3-SiO2 aerogel still decrease significantly with increasing temperature. In order to improve the high-temperature thermal stability of Al2O3-SiO2 aerogel, heteroatom doping and modifier modification methods can be used.
[0003] Patent CN201310276044.2 discloses that the acetone-aniline in-situ water method is used to control the hydrolysis-polycondensation rate of aluminum alkoxide to obtain a uniform alumina gel, the alumina gel is supercritically modified with aluminum sec-butylate and ethyl orthosilicate hydrolyzate, and the alumina aerogel is gas-phase modified with hexamethyldisilazane to prepare a silicon-modified alumina aerogel, which shrinks linearly by 5% after being treated at 1200°C for 2h, and the specific surface area reaches 280m 2 / g, and no α phase transformation occurs. However, the aniline used in the preparation process is highly toxic, the supercritical modification process is relatively complicated and requires a large amount of hydrolyzate and drying medium.
[0004] Patent CN201310276044.2 discloses that during the preparation of the sol, an alumina sol is obtained by high temperature sealing treatment, and an appropriate amount of silicon source precursor is added to the sol, and silicon-modified alumina aerogel is obtained by supercritical ethanol. The initial (after drying) specific surface area of the silicon-modified alumina aerogel is 312m 2 / g or more. After being treated at 1200, 1300, and 1400℃ for 2h, the specific surface areas of the aerogels were 226, 177, and 64m2, respectively. 2 / g. Its initial specific surface area is not high enough, and the determination of thermal insulation performance is not mentioned in the patent literature.
[0005] So far, the high temperature resistance modification of Al2O3-SiO2 aerogel has only focused on heat resistance, but not on the improvement of thermal insulation performance. How to improve the high temperature resistance and thermal insulation performance of Al2O3-SiO2 aerogel has become one of the hot topics in the research field of Al2O3-SiO2 aerogel. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a high-performance, high-temperature resistant double-modified Al2O3-SiO2 composite aerogel and a preparation method thereof. The composite aerogel prepared by the present invention has high specific surface area, high pore volume and thermal insulation performance; at the same time, it also has a heat resistance of up to 1200°C.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel, comprising the following steps:
[0009] S1. The tetraethyl orthosilicate, the organosilane modifier, and the ethanol are mixed and then water and an acid catalyst are added to hydrolyze to obtain a mixed solution A;
[0010] S2. Aluminum chloride, water and ethanol are mixed and hydrolyzed to obtain a mixed solution B;
[0011] S3. The mixed solution B and the mixed solution A are mixed and stirred to obtain a modified precursor sol;
[0012] S4. mixing the precursor sol with a coagulant to obtain a modified composite wet gel;
[0013] S5. The composite wet gel is deposited and modified in an aging deposition liquid to obtain a double-modified composite wet gel;
[0014] S6. Drying the double-modified composite wet gel to obtain a high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel.
[0015] Preferably, the molar ratio of tetraethyl orthosilicate, organosilane modifier, ethanol, water and acid catalyst in S1 is 1:(0.5-3):(3-15):(3-15):(0.01-0.03). The present invention adopts the above technical scheme, adds organosilane modifier in the stage of preparing aerogel sol, realizes co-precursor modification and optimizes the gel network structure, changes the crosslinking degree of the three-dimensional network structure of the material, and improves the physical properties of the aerogel, with low thermal conductivity and good thermal insulation performance.
[0016] Preferably, the organosilane modifier is one or more of methyltriethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane or tetramethylsilane; further preferably, the organosilane modifier is methyltriethoxysilane or dimethyldiethoxysilane.
[0017] Preferably, the acid catalyst is hydrochloric acid, nitric acid, oxalic acid or acetic acid; more preferably, the acid catalyst is hydrochloric acid or nitric acid.
[0018] Preferably, the hydrolysis time in S1 is 2 to 5 hours;.
[0019] Preferably, the molar ratio of aluminum chloride, water and ethanol in S2 is 1:(0-6):(4-12).
[0020] Preferably, the hydrolysis time in S2 is 3 to 6 hours.
[0021] Preferably, the mixing and stirring time in S3 is 6 to 18 hours.
[0022] Preferably, the molar ratio of tetraethyl orthosilicate, organosilane modifier and aluminum chloride in the modified precursor sol in S3 is 1:(0.25-3):(1-8). In the present invention, the mixed solution A and the mixed solution B are further mixed to prepare the aerogel material, and when the mixed solution of the two satisfies the above ratio, a good effect is achieved.
[0023] Preferably, the mass ratio of the precursor sol to the coagulant in S4 is 3 to 5:1.
[0024] Preferably, the coagulant is 1,2-propylene oxide.
[0025] Preferably, the aging deposition liquid in S5 is obtained by mixing ethanol and an organic silane modifier in a molar ratio of 1:0.1 to 3. The present invention further improves the performance of the gel material during the aging stage by adopting the above technical solution; because aging is usually used to further condense, crosslink and reinforce the gel network when preparing aerogel materials, the mechanical strength of the gel can be enhanced, the uniformity of the pore structure can be improved, and the performance of the final product can be improved. The inventors of the present invention have found that the hydroxyl groups on the surface of the material are replaced by silane groups by adopting deposition modification to replace the gel surface groups during the aging stage, so that the hydroxyl groups that are prone to severe condensation at high temperatures are replaced by more high-temperature resistant silane groups, which can largely preserve the mesoporous structure of the aerogel. At the same time, since it is difficult to grow Al2O3 particles in a SiO2 matrix, the phase transition temperature of the aerogel is significantly improved.
[0026] More preferably, the organosilane modifier used in the aged deposition solution is one or more of methyltriethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane or tetramethylsilane.
[0027] Preferably, the aging time in S5 is 72 to 148 hours.
[0028] Preferably, the drying in S6 is carried out by supercritical fluid drying;
[0029] The volume ratio of the drying medium to the double-modified composite wet gel is 0.1-0.5:1, the pressure of supercritical fluid drying is 2-5 MPa, the temperature is 250-280° C., and the insulation time is 0.5-2 h;
[0030] The supercritical fluid drying medium is ethanol.
[0031] In a second aspect, the present invention provides a high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel prepared by the above-mentioned preparation method.
[0032] Contains at least the following beneficial technical effects:
[0033] The present invention adds organosilane, realizes co-precursor modification and optimizes gel network structure by adding organosilane in the sol stage, and adopts deposition modification and replacement of gel surface groups in the aging stage to prepare high-performance and high-temperature resistant double-modified Al2O3-SiO2 aerogel; the present invention adds organosilane in the sol stage and the aging stage, and improves the comprehensive performance of the final aerogel material through different effects on the two stages.
[0034] First, the physical properties of aerogel are improved, the thermal conductivity is low, and the thermal insulation performance is good. After testing, the specific surface area of the double-modified Al2O3-SiO2 composite aerogel at room temperature is 596.3m 2 / g, pore volume is 3.462cm 3 / g, thermal conductivity is 0.029Wm -1 K -1 The specific surface area of unmodified Al2O3-SiO2 aerogel at room temperature is 392.5m 2 / g, pore volume 1.125cm 3 / g, thermal conductivity 0.037Wm -1 K -1 .
[0035] Secondly, the high temperature resistance is significantly improved. After calcination at 1200℃, the crystallinity and crystal plane types are significantly reduced. These significantly improve the high temperature stability of the material. After heat treatment at 1200℃ in an oxygen environment, the optimal specific surface area of the high-performance high temperature resistant double modified Al2O3-SiO2 composite aerogel is 219.6m 2 / g, and the optimal pore volume is 1.768cm 3 / g, thermal conductivity is 0.046Wm -1 K -1 , which is much better than the specific surface area of 181.3m2 of the unmodified Al2O3-SiO2 composite aerogel after heat treatment at 1200℃ in an oxygen environment. 2 / g, pore volume is 0.962cm 3 / g, thermal conductivity 0.121Wm -1 K -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a process flow chart for preparing the high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel of the present invention;
[0037] Figure 2 This is a scanning electron microscope microscopic morphology image of the composite aerogel prepared in Example 1 of the present invention;
[0038] Figure 3 This is a scanning electron microscope microscopic morphology image of the composite aerogel prepared in Example 1 of the present invention after heat treatment at 1200°C.
[0039] Figure 4 The pore size distribution comparison diagram of aerogels prepared in Example 1 of the present invention and Comparative Example 1 is shown.
[0040] Figure 5 This is a comparison chart of the pore size distribution of the aerogels prepared in Example 1 of the present invention and in Comparative Example 1 after heat treatment at 1200°C. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] The "room temperature" and "normal temperature" mentioned in the present invention are all calculated as 25±2°C unless otherwise specified.
[0047] The raw materials and instruments used in the following examples of the present invention are commercially available unless otherwise specified.
[0048] Example 1
[0049] This embodiment provides a high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel, and the preparation steps are as follows:
[0050] (1) Preparation of precursor-modified Al2O3-SiO2 sol:
[0051] Tetraethyl orthosilicate, dimethyldiethoxysilane and ethanol were mixed, and then water and hydrochloric acid were added to hydrolyze for 3 hours to obtain a mixed solution A;
[0052] Aluminum chloride, water and ethanol were mixed and hydrolyzed for 5 hours to obtain a mixed solution B;
[0053] Mixing the mixed solution A and the mixed solution B and stirring them for 12 hours to obtain a modified precursor sol;
[0054] The molar ratio of tetraethyl orthosilicate, dimethyldiethoxysilane, aluminum chloride, water, ethanol and hydrochloric acid in the modified precursor sol is 1:2:4:6:6:0.002.
[0055] (2) Gel:
[0056] The coagulant 1,2-propylene oxide is added dropwise to the modified precursor sol in a ratio of 3:1, and the coagulant is gradually added in an amount that ensures that it can gel within 10 minutes to obtain a modified composite wet gel.
[0057] (3) Aging and deposition modification:
[0058] The modified composite wet gel was added into an aging deposition solution and soaked for 72 hours to obtain a double-modified composite wet gel; wherein the aging deposition solution used was a mixture of ethanol and methyltriethoxysilane in a volume ratio of 1:1.
[0059] (4) Supercritical drying:
[0060] Place the double-modified composite wet gel into a supercritical fluid drying device, add a drying medium to immerse the colloid, pre-fill with nitrogen to 3.5MPa, heat to 270℃, and keep warm for 1h. Slowly release the pressure and flush with N2 for 5 times to obtain a high-performance, high-temperature resistant double-modified Al2O3-SiO2 composite aerogel.
[0061] The specific surface area of the high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel was measured to be 585.3 m 2 / g, pore volume is 3.362cm 3 / g, thermal conductivity 0.030Wm -1 K -1 ; After calcination at 1200℃, the specific surface area is 218.4m 2 / g, pore volume is 1.694cm 3 / g, thermal conductivity 0.047Wm -1 K -1 .
[0062] Example 2
[0063] This embodiment provides a high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel, and the preparation steps are as follows:
[0064] (1) Preparation of precursor-modified Al2O3-SiO2 sol:
[0065] Tetraethyl orthosilicate, trimethylethoxysilane, dimethyldiethoxysilane and ethanol are mixed, and then water and hydrochloric acid are added to hydrolyze for 5 hours to obtain a mixed solution A;
[0066] Aluminum chloride, water and ethanol were mixed and hydrolyzed for 3 hours to obtain a mixed solution B;
[0067] Mixing the mixed solution A and the mixed solution B and stirring them for 16 hours to obtain a modified precursor sol;
[0068] The molar ratio of tetraethyl orthosilicate, trimethylethoxysilane, dimethyldiethoxysilane, aluminum chloride, water, ethanol and hydrochloric acid in the modified precursor sol is 1:1:1:8:6:6:0.002.
[0069] (2) Gel:
[0070] The coagulant 1,2-propylene oxide is added dropwise to the modified precursor sol at a ratio of 4:1, and the coagulant is gradually added in an amount that ensures that it can gel within 10 minutes to obtain a modified composite wet gel.
[0071] (3) Aging and deposition modification:
[0072] The modified composite wet gel was added into an aging deposition solution and soaked for 120 hours to obtain a double-modified composite wet gel; wherein the aging deposition solution used was a mixture of ethanol and methyltriethoxysilane in a volume ratio of 1:2.
[0073] (4) Supercritical drying:
[0074] The aged colloid in step (3) was placed in a supercritical fluid drying device, and a drying medium was added to immerse the colloid. Nitrogen was pre-filled to 4 MPa, and then heated to 270°C and kept warm for 1.5 hours. The pressure was slowly released, and N2 was flushed 10 times to obtain a high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel.
[0075] The high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel has a specific surface area of 541.8 m 2 / g, pore volume is 2.134cm 3 / g, thermal conductivity 0.029Wm -1 K -1 ; After calcination at 1200℃, the specific surface area is 209.1m 2 / g, pore volume is 1.481cm 3 / g, thermal conductivity 0.051Wm -1 K -1 .
[0076] Example 3
[0077] This embodiment provides a high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel, and the preparation steps are as follows:
[0078] (1) Preparation of precursor-modified Al2O3-SiO2 sol:
[0079] Tetraethyl orthosilicate, trimethylethoxysilane and ethanol are mixed, and then water and hydrochloric acid are added to hydrolyze for 5 hours to obtain a mixed solution A;
[0080] Aluminum chloride, water and ethanol were mixed and hydrolyzed for 5 hours to obtain a mixed solution B;
[0081] Mixing the mixed solution A and the mixed solution B and stirring them for 10 hours to obtain a modified precursor sol;
[0082] The molar ratio of tetraethyl orthosilicate, trimethylethoxysilane, aluminum chloride, water, ethanol and hydrochloric acid in the modified precursor sol is 1:0.5:1:6:6:0.002.
[0083] (2) Gel:
[0084] The coagulant 1,2-propylene oxide is added dropwise to the modified precursor sol at a ratio of 5:1, and the coagulant is gradually added in an amount that ensures that it can gel within 10 minutes to obtain a modified composite wet gel.
[0085] (3) Aging and deposition modification:
[0086] The modified composite wet gel was added to an aging deposition solution and soaked for 72 hours to obtain a double-modified composite wet gel; wherein the aging deposition solution used was a mixture of ethanol and tetramethylsilane in a volume ratio of 1:1.5.
[0087] (4) Supercritical drying:
[0088] The aged colloid in step (3) was placed in a supercritical fluid drying device, and a drying medium was added to immerse the colloid. Nitrogen was pre-filled to 5 MPa, and then heated to 260°C and kept warm for 2 hours. The pressure was slowly released, and N2 was flushed 8 times to obtain a high temperature resistant double modified Al2O3-SiO2 composite aerogel.
[0089] The specific surface area of the high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel was measured to be 531.2 m 2 / g, pore volume is 2.632cm 3 / g, thermal conductivity 0.032Wm -1 K -1 ; After calcination at 1200℃, the specific surface area is 214.5m 2 / g, pore volume is 1.562cm 3 / g, thermal conductivity 0.053Wm -1K -1 .
[0090] Comparative Example 1
[0091] Preparation of unmodified Al2O3-SiO2 composite aerogel:
[0092] The molar ratio of tetraethyl orthosilicate, aluminum chloride, water, ethanol and hydrochloric acid in the precursor solution of this embodiment is 1:4:6:6:0.002; the aging solution used is ethanol.
[0093] The specific preparation steps are as follows:
[0094] (1) Preparation of Al2O3-SiO2 precursor sol:
[0095] Aluminum chloride, tetraethyl orthosilicate, and ethanol solvent were first mixed for 0.5 h, and then deionized water and hydrochloric acid were added for hydrolysis for 6 h to obtain unmodified Al2O3-SiO2 sol.
[0096] (2) Gel:
[0097] Add 1,2-propylene oxide, a coagulant, dropwise to the unmodified Al2O3-SiO2 sol prepared in step (1), and gradually add the coagulant in an amount that ensures that the sol can gel within 10 minutes to obtain an unmodified Al2O3-SiO2 composite wet gel.
[0098] (3) Aging but not deposition modification:
[0099] The unmodified Al2O3-SiO2 composite wet gel prepared in step (2) was added to the aging solution and soaked for 72 hours.
[0100] (4) Supercritical drying:
[0101] The aged colloid in step (3) was placed in a supercritical fluid drying device, and a drying medium was added to immerse the colloid. Nitrogen was pre-filled to 3.5 MPa, and then heated to 270°C and kept warm for 1 hour. The pressure was slowly released, and N2 was flushed 5 times to obtain an unmodified Al2O3-SiO2 composite aerogel.
[0102] The unmodified Al2O3-SiO2 composite aerogel has a specific surface area of 392.5 m 2 / g, pore volume is 1.125cm 3 / g, thermal conductivity 0.037Wm -1 K -1 ; After calcination at 1200℃, the specific surface area is 181.3m 2 / g, pore volume is 0.962cm 3 / g, thermal conductivity 0.121Wm -1 K -1 .
[0103] Comparative Example 2
[0104] The preparation method of this comparative example is the same as that of the embodiment, except that no organosilane modifier is added during the sol preparation stage in step (1).
[0105] The unmodified Al2O3-SiO2 composite aerogel has a specific surface area of 408.6 m 2 / g, pore volume is 1.597cm 3 / g, thermal conductivity 0.035Wm -1 K -1 ; After calcination at 1200℃, the specific surface area is 190.5m 2 / g, pore volume is 1.022cm 3 / g, thermal conductivity 0.108Wm -1 K -1 .
[0106] Comparative Example 3
[0107] The preparation method of this comparative example is the same as that of the embodiment, except that no organosilane modifier is added during the aging stage in step (3).
[0108] The unmodified Al2O3-SiO2 composite aerogel has a specific surface area of 415.9 m 2 / g, pore volume is 1.476cm 3 / g, thermal conductivity 0.031Wm -1 K -1 ; After calcination at 1200℃, the specific surface area is 195.3m 2 / g, pore volume is 1.128cm 3 / g, thermal conductivity 0.116Wm -1 K -1 .
[0109] Based on the embodiments and comparative examples, the double modification strategy adopted in the present invention can significantly improve the physical properties and high temperature resistance of aerogel materials; although the performance will be partially improved for modification in the sol or gel stage alone, it is far less than the improvement brought by the double modification.
[0110] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel, characterized in that: The following steps are involved: S1. The tetraethyl orthosilicate, the organosilane modifier, and the ethanol are mixed and then water and an acid catalyst are added to hydrolyze to obtain a mixed solution A; S2. Aluminum chloride, water and ethanol are mixed and hydrolyzed to obtain a mixed solution B; S3. The mixed solution B and the mixed solution A are mixed and stirred to obtain a modified precursor sol; S4. mixing the precursor sol with a coagulant to obtain a modified composite wet gel; S5. The composite wet gel is deposited and modified in an aging deposition liquid to obtain a double-modified composite wet gel; S6. Drying the double-modified composite wet gel to obtain a high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel.
2. The preparation method according to claim 1, characterized in that: The molar ratio of tetraethyl orthosilicate, organic silane modifier, ethanol, water and acid catalyst in S1 is 1:(0.5-3):(3-15):(3-15):(0.01-0.03).
3. The preparation method according to claim 2, characterized in that: The organosilane modifier is one or more of methyltriethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane or tetramethylsilane.
4. The preparation method according to claim 2, characterized in that: The acid catalyst is hydrochloric acid, nitric acid, oxalic acid or acetic acid.
5. The preparation method according to claim 1, characterized in that: The molar ratio of aluminum chloride, water and ethanol in S2 is 1:(0-6):(4-12).
6. The preparation method according to claim 1, characterized in that: The molar ratio of tetraethyl orthosilicate, organic silane modifier and aluminum chloride in the modified precursor sol in S3 is 1:(0.25-3):(1-8).
7. The preparation method according to claim 1, characterized in that: The mass ratio of the precursor sol to the coagulant in S4 is 3 to 5:1; The coagulant is 1,2-propylene oxide.
8. The preparation method according to claim 1, characterized in that: The aged deposition liquid in S5 is obtained by mixing ethanol and an organic silane modifier in a molar ratio of 1:0.1 to 3.
9. The preparation method according to claim 1, characterized in that: The drying in S6 is carried out by supercritical fluid drying; The volume ratio of the drying medium to the double-modified composite wet gel is 0.1-0.5:1, the pressure of supercritical fluid drying is 2-5 MPa, the temperature is 250-280° C., and the insulation time is 0.5-2 h; The supercritical fluid drying medium is ethanol.
10. A high-performance, high-temperature-resistant double-modified Al2O3-SiO2 composite aerogel, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of high temperature-resistant alumina aerogel material
CN103342537B